The impact of foreign and independent commissioners on bank performance: empirical evidence from Indonesia - Zakaria, Adam; Mardiyati, Umi; Pena, Cassania Dela (Ifma Publishing, 2022)
The purpose of this study is to empirically prove the influence of foreign commissioners and independent commissioners on bank performance. This research is a quantitative study using secondary data in the form of annual reports issued by companies in the banking sector. The research sample is banking companies in the 2010-2019 period. The results of the study show that foreign commissioners have a significant negative effect on bank performance with ROA and ROE proxies and have a significant positive effect on bank performance with NIM proxies. Meanwhile, independent commissioners have no influence on bank performance using either ROA, ROE, or NIM proxies.